2016
DOI: 10.3109/14756366.2015.1132711
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biochemical characterization of glucose 6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase and glutathione reductase from rat lung and inhibition effects of some antibiotics

Abstract: G6PD, 6PGD and GR have been purified separately in the single step from rat lung using 2 0 , 5 0 -ADP Sepharose 4B affinity chromatography. The purified enzymes showed a single band on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The molecular weights of the enzymes were estimated to be 134 kDa for G6PD, 107 kDa for 6PGD and 121 kDa for GR by Sephadex G-150 gel filtration chromatography, and the subunit molecular weights was respectively found to be 66, 52 and 63 kDa by SDS-PAGE. Optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The results indicated that the G6PD, 6PGD, and GR enzymes are homodimers. Similar results have been observed for rat kidney, rat lung, rat heart, trout liver, human erythrocytes, and calf liver …”
Section: Discussionsupporting
confidence: 88%
“…The results indicated that the G6PD, 6PGD, and GR enzymes are homodimers. Similar results have been observed for rat kidney, rat lung, rat heart, trout liver, human erythrocytes, and calf liver …”
Section: Discussionsupporting
confidence: 88%
“…Similarly inhibitory effects of some antibiotics on purified rat lung G6PD, 6PGD, and GR enzymes were investigated. Levofloxacin, furosemide, ceftazidime, cefuroxime, and gentamicin were found to exert inhibition on enzyme activity . In another study, inhibitory effects of some metals on GR enzyme purified from human erythrocytes .…”
Section: Discussionmentioning
confidence: 91%
“…Similarly 6‐phosphogluconate dehydrogenase, catalyzes third reaction in the same pathway and converts 6‐phosphogluconate into d ‐ribulose 5‐phosphate in the presence of NADP + . GR enzyme, which is a member of oxidoreductase enzyme family, converts oxidized glutathione into reduced glutathione . TrxR belongs to pyridine nucleotide disulfate oxidoreductase flavonoid family.…”
Section: Discussionmentioning
confidence: 99%
“…NADPH inhibits 6PGD, so it has a negative mechanism. Again, the optimum pHi for this enzyme is alkaline [ 43 , 44 ].…”
Section: Oxidative Phasementioning
confidence: 99%